2002
DOI: 10.2337/diabetes.51.8.2377
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory Effects of HMG CoA Reductase Inhibitor and Fish Oils on Apolipoprotein B-100 Kinetics in Insulin-Resistant Obese Male Subjects With Dyslipidemia

Abstract: Hepatic accumulation of lipid substrates perturbs apolipoproteinB-100 (apoB) metabolism in insulin-resistant, obese subjects and may account for increased risk of cardiovascular disease. In a placebo-controlled trial, we examined the independent and combined effects of decreasing cholesterol synthesis with atorvastatin (40 mg/day) and triglyceride synthesis with fish oils (4 g/day) on apoB kinetics. The subjects were 48 viscerally obese, insulin-resistant men with dyslipidemia who were studied in a fasted stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
102
0
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 152 publications
(111 citation statements)
references
References 53 publications
8
102
0
1
Order By: Relevance
“…VLDL, IDL, and LDL were isolated from 3 ml plasma by sequential ultracentrifugation (Optima XL-100K; Beckman Coulter, Fullerton, Australia) at densities of 1.006, 1.019, and 1.063 g/ml, respectively. The procedures for isopropranol precipitation, delipidation, hydrolysis, and derivatization of apoB to the oxazolinone derivative were described previously (9,30). Plasmafree leucine was also isolated by cation-exchange chromatography using AG 50 W-X8 resin (BioRad, Richmond, CA) after removing plasma proteins with 60% perchloric acid.…”
Section: Subjectsmentioning
confidence: 99%
See 2 more Smart Citations
“…VLDL, IDL, and LDL were isolated from 3 ml plasma by sequential ultracentrifugation (Optima XL-100K; Beckman Coulter, Fullerton, Australia) at densities of 1.006, 1.019, and 1.063 g/ml, respectively. The procedures for isopropranol precipitation, delipidation, hydrolysis, and derivatization of apoB to the oxazolinone derivative were described previously (9,30). Plasmafree leucine was also isolated by cation-exchange chromatography using AG 50 W-X8 resin (BioRad, Richmond, CA) after removing plasma proteins with 60% perchloric acid.…”
Section: Subjectsmentioning
confidence: 99%
“…Quantification of apoB, apoAI, and other analytes. Plasma aliquots were combined to yield five pooled VLDL, IDL, and LDL samples per patient study, as described previously (30). ApoB was isolated in each lipoprotein fraction using isopropanol and quantitated with the Lowry method (9,30).…”
Section: Subjectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Davidson et al (96) found that after treating HC patients with n-3 PUFA and/or simvastatin for 12 weeks, the TAG responses were similar in the EPA/DHA-group (2 25·3 %) and the combined group (2 28·8 %), and borderline significantly lower in the simvastatin group (2 18·5 %), whereas decreases in non-HDL-cholesterol and increases in HDL-cholesterol were statistically significant only for the combined (non-HDL: 2 24·8 %, HDL: þ10·4 %) and simvastatin group (non-HDL: 2 25·8 %, HDL: þ7·2 %). All other studies found significant improvements of TAG with a combination therapy compared with the statin therapy alone (94,95,97,99,104) . Study populations included, besides HC patients, renal transplant patients with persistent hypercholesterolaemia (99) and insulin-resistant obese men with dyslipidaemia (95) .…”
Section: Effects Of Combination Therapy With N-3 Pufa and Statinsmentioning
confidence: 93%
“…The authors suggest that the two compounds reduce TAG levels through different mechanisms. Whereas n-3 PUFA reduced the hepatic secretion of VLDL-apoB, atorvastatin enhanced the clearance of all apo B-containing lipoproteins, resulting in an additive effect (94,95) . Aligeti et al performed a retrospective cohort study in which they compared the change in plasma TAG levels between patients taking fish oil as monotherapy and patients who added fish oil to their usual lipid-lowering Table 7.…”
Section: Effects Of Combination Therapy With N-3 Pufa and Statinsmentioning
confidence: 99%